How Positionality of Students Influences the Learning by the “Junior Year Abroad Program” at Tamkang University, Taiwan - Jannette Wei-Ting (Adult Education Research Conference, 2010)
The purpose of this is to better understand and deeper explore how the positionalities of students of Tamkang University shape their intercultural learning experiences in their Junior Abroad year. Three conclusions found in the study: Political identity as an important element, being ignored and powerless in the classroom and Personal Growth gained through the JYAP.